ANALISIS PERUBAHAN LUAS LAHAN MANGROVE DI KABUPATEN POHUWATO PROPINSI GORONTALO DENGAN MENGGUNAKAN CITRA LANDSAT - Opa, Esry T (JURNAL PERIKANAN DAN KELAUTAN TROPIS, 2010)
A study on spatial evaluation of mangrove resource was carried out in Pohuwato Regency, the province of Gorontalo, for 3 months. The mangrove resources in this area have been exploited to build ponds, houses and for firewood. As the result, there was a significant decrease in mangrove population. In this study, main data were gathered from Landsat TM Satellite Image 2000-2001 and 2009-2010, and others data collected from the field and interviews with local villagers. Aproximately 60 sampling points were observed and examined. Normalized Difference Vegetation Index (NDVI) was applied to determine the extent of mangroves and its changes. In 2000-2001, the mangrove area was about 7,007.67 Ha, and reduced to 3,034.53 Ha in 2009-2010.